A national survey of automated external defibrillator provision and training at secondary schools in Wales. (November 2017) - Phillips, Thom I; Martin, Rhodri; Ellis, Gethin
Abstract: Background: Every week, 12 young people die from undiagnosed heart conditions in the UK. The role of mass cardiac screening in prevention is controversial (on clinical and cost-effectiveness grounds) and is not consistent with the principle of prudent health care. Several cases have shown that these deaths could be preventable through prompt delivery of basic life support with defibrillation using an automated external defibrillator (AED). An individual's chance of survival after cardiac arrest decreases by around 10% for every minute of delay in commencing treatment. The aim of the study was to establish the number of schools that had an AED on site and suitably trained staff. Methods: Sport Wales' School Sport Survey is an annual online survey. It is compulsory for all publicly funded schools in Wales and collects data about students' participation in sports and provision of physical education. In collaboration with Sport Wales, five additional questions were added with the aim of ascertaining the number of schools that had access to an AED and staff trained in basic life support and AED operation. Data were collected between April 13 and July 21, 2015. School data included the Welsh Index of Multiple Deprivation to evaluate how socioeconomic factors influenced training and AED availability. Findings: 207 schools were included in the analysis. 52 schools reported using either basic life support or an AED at least once in the previous 5 years. 128 schools (62%) had no access to an AED. 81 schools reported that they had no teachers with basic life support training. 50 of the schools with staff trained in basic life support did not have AED training. Schools in the most deprived areas were less likely than those in the least deprived areas to have access to an AED and have teachers with basic life support or AED training (47/124 vs 43/72, p=0·035). Interpretation: Only a small number of secondary schools in Wales have teachers who are trained in basic life support and have access to an AED. Schools in the local authorities with the lowest Welsh Index of Multiple Deprivation were significantly less likely to have access to an AED and suitably trained staff. Providing all teachers in Wales with basic life support training and supplying AEDs to all secondary schools may be a cost-effective health-care intervention. Funding: No funding sources to declare.